Multilateral development banks: financial constraints and counter-cyclical mandate - Molinari, Andrea (2020)
Over the last decades, and given their attractiveness as financing sources for developing countries, multilateral development banks (MDBs) have grown (in quantity and size) supported by their particular funding sources. Such resource dependence has not been sufficiently problematised in the MDB literature, especially in terms of these organisations? credit exposure with their larger (middle-income) borrowing members. In this paper, we identify and characterise the three MDBs? funding sources that constitute their resource dependence: capital contributions, bond issuing leverage and borrower dynamics. Further, we analyse these sources for the International Development Bank, Inter-American Development Bank (IDB) and African Development Bank. Finally, we deepen our analysis to look into two recent events: the risk swap implemented by these MDBs (in 2015) and the effect of Argentina´s selective default upon the IDB?s capital adequacy (2014-2015). We find that market leverage and borrower dynamics dimensions have grown in relevance, hence re-configuring a resource dependence that weakens MDB?s development mandate.